The Future of Interventions for Stage IV Colorectal Cancers - Lloy, Samantha; Lin, Mayin; Franko, Jan; Raman, Shankar (Clinics in Colon and Rectal Surgery, 2023)
Future options for the management of stage IV colorectal cancer are primarily focused on personalized and directed therapies. Interventions include precision cancer medicine, utilizing nanocarrier platforms for directed chemotherapy, palliative pressurized intraperitoneal aerosol chemotherapy (PIPAC), adjunctive oncolytic virotherapy, and radioembolization techniques. Comprehensive genetic profiling provides specific tumor-directed therapy based on individual genetics. Biomimetic magnetic nanoparticles as chemotherapy delivery systems may reduce systemic side effects of traditional chemotherapy by targeting tumor cells and sparing healthy cells. PIPAC is a newly emerging option for patients with peritoneal metastasis from colorectal cancer and is now being used internationally, showing promising results as a palliative therapy for colorectal cancer. Oncolytic virotherapy is another emerging potential treatment option, especially when combined with standard chemotherapy and/or radiation, as well as immunotherapy. And finally, radioembolization with yttrium-90 (90Y) microspheres has shown some success in treating patients with unresectable liver metastasis from colorectal cancer via selective arterial injection.
Keywords: colorectal cancer; precision cancer medicine; targeted genomic cancer therapy; oncolytic virotherapy; pressurized intraperitoneal aerosol chemotherapy (PIPAC); yttrium-90 (90Y) microsphere radioembolization